Numerical Simulation of Wetting Phenomena with a Phase‐Field Method Using OpenFOAM®. Issue 11 (17th August 2015) - Cai, Xuan; Marschall, Holger; Wörner, Martin; Deutschmann, Olaf
Abstract: The phase‐field method coupled with the Navier‐Stokes equations is a rather new approach for scale‐resolving numerical simulation of interfacial two‐phase flows. The intention is to implement it as finite‐volume method in the open source library for computational continuum mechanics OpenFOAM® and make it freely available. An overview on the governing equations is given and the numerical method is shortly discussed. The focus is on application and validation of the code for some fundamental wetting phenomena, namely the capillary rise in a narrow channel and the spreading of a droplet on a flat surface, which is chemically homogeneous or regularly patterned. The numerical results on static meshes agree well with analytical solutions and experimental/numerical results from literature. Also, first 3D finite‐volume simulations with adaptive mesh refinement near the interface are presented as a key element to achieve CPU‐time efficient simulations. Abstract : A phase‐field method for interface resolving numerical simulations of two‐phase flows is presented and implemented in OpenFOAM®. The method is validated for several capillary flows with moving contact lines and is used to study dynamic droplet spreading on a flat surface by three‐dimensional simulations with adaptive mesh refinement near the interface.